Analysis of Regional Original Revenues and Routine Expenditures on Regional Financial Performance in East Java Regencies and Cities: Analysis of Regional Original Revenues and Routine Expenditures on Regional Financial Performance in East Java Regencies and Cities - Muhammad Yasin (Jurnal Mantik, 2020)
Economic growthis the process of change in a country's economy sustainably towards a better state for a certain period. Economic growth can be defined as well as the increase in production capacity of an economy that is realized in the form of increase in national income.Variables PAD (X1) is measured using: (1) taxes, (2) Non tax, recurrent (X2) is measured using: (1) Direct, (2) Not immediately. The financial performance of the independent variable region (Y) is measured using: (1) The efficiency ratio, (2) Ratio Effectiveness, (3) Ratio of independence, (4) The ratio of the economic aktivitas.pertumbuhan This means that if the local revenue, it will cause an increase in Similarly to the achievement of economic growth. highly flexible in terms of utilization, an area of ??more flexibility in planning the budget allocation for development activities in accordance with its economic agenda which include the construction of basic facilities and infrastructure that play a role in supporting the optimal economic growth.